PENGARUH KONFLIK KERJA, KOMUNIKASI DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PADA PERUSAHAAN TRANSPORTASI PT. BENGAWAN SOLO TRANS - Radhitya Auzora; M. Farid Wajdi (Sekolah Tinggi Teknologi Kedirgantaraan, 2024)
The purpose of this study was to analyze the effect of work conflict, communication and work environment on employee performance at the transportation company PT Bengawan Solo Trans. This research method is quantitative. The type of data used in this research is primary data. Primary data used in this study were obtained from answers to questionnaires given by each respondent, namely all employees of PT Batik Solo Trans Surakarta. The population in this study were all drivers at PT Batik Solo Trans Surakarta, totaling 138 people. Sampling was done by meeting the driver and asking for his willingness to fill out a questionnaire. The sampling technique in this study used saturated sampling or total sampling. So, all members of the population were sampled, namely 138 drivers. The data analysis technique was carried out with the help of the SPSS for Windows computer program. The results of this study are that work conflict has a negative and significant effect on employee performance of PT BST Surakarta. Communication has a positive and significant effect on the performance of employees of PT BST Surakarta. Work environment has a positive and significant effect on the performance of employees of PT BST Surakarta. Work conflict, communication, and work environment together have a significant effect on the performance of employees of PT. BST Surakarta.